地中熱ヒートポンプ暖房システムの性能予測および設計ツールの開発 - 佐々木, 正史; 金野, 彩佳; 服部, 裕太; 遠藤, 登 (Transactions of the JSME (in Japanese), 2015)
A ground source heat pump (GSHP) heating system is one of the most effective and realistic renewable energy plants which reduce energy consumption and carbon dioxide to be about a half in comparison with an oil heater in cold climate region. In spite of such superior performance, utilization of GSHP has not been extended in Japan, while that has been remarkably increased in Europe and USA. A design tool which is easy to use for builders is required in Japan. Energy balances in an actual renewable energy house, equipped with a GSHP air conditioning system were observed by real-time continuous monitoring systems from 2005 to 2013 and analyzed in Kitami City, Hokkaido, subarctic region, Japan. Real-time continuous monitoring of soil temperature distributions were also carried out from July in 2007. Thermal demand of heating (=heat loss) from house and thermal input caused by residents were well predicted using house configurations and meteorological data (mainly ambient temperature and wind speed). We set the allowable lowest soil temperature at the vicinity of a heat collecting tube 0°C under a common ambient temperature condition in order to maintain healthiness of soil. Seasonal and cumulative changes in soil temperature distributions were successfully analyzed with FEM from the beginning of GSHP operation in 2005 to the end of that in spring, 2014. A prediction method of required lengths of a U-tube to the required heating demands in various domestic cities which have various soil temperatures has been developed. Builders will easily use these simplified methods as a new design tool. journal article